‘Inner Gardens’ of Tel Aviv: The Implementation of Urban Utopia by Patrick Geddes - Leonova, Yulia V. (Actual Problems of Theory and History of Art, 2018)
The founders of Tel Aviv envisioned it in 1909 as an exemplary Garden City to ‘blossom in the sands’. In 1925, Patrick Geddes, a Scottish urban planner and the theorist of garden city ideas, was invited to plan the rapidly growing city. Among the key features of his plan were so-called ‘home-blocks’, i.e. residential structures with inner gardens, which are the subject of the present paper. There is no agreement whether or not Geddes’ Gardens of Tel Aviv should be considered as implemented. There has been no special research on this subject, especially in the art historical context.After archival research, studying the maps and exploring in situ, the author found approximately twenty sites which can be definitely connected with Geddes’ ideas. In this paper, the author briefly describes her conclusions on newly discovered ‘Geddes Gardens’ features such as shape, urban connection, pedestrian lanes, landscape, historical and art objects, as well as their connections with the history of urbanism, Garden City, and Modern Movement ideas.
Keywords: garden city; Patrick Geddes; Tel Aviv; Modern Movement; town planning; environmentalism